Multimedia English Learning Materials for Deaf or Hard of Hearing (DHH) Children - Adnyani, Ni Luh Putu Sri; Wisudariani, Ni Made Rai; Pradnyana, Gede Aditra; Pradnyana, I Made Ardwi; Suwastini, Ni Komang Arie (Universitas Pendidikan Ganesha, 2021)
In supporting learning for Deaf or Hard of Hearing/DHH children, it is not easy finding learning sources that are accessible online, especially in English. Furthermore, during the COVID-19 pandemic, when learning was required to be carried out online, there were no learning applications that included English sign language that could be used by teachers and students as learning media. Thus, this study aims to analyze the need for developing multimedia-based English learning materials for Deaf or Hard of Hearing (DHH) children. This qualitative study involved DHH students and instructors in Special School (SLB), Bali. The need analysis was conducted to identify the ongoing situation of DHH children in the context of developing English multimedia learning materials. Interview and observation techniques applying two types of instruments in the form of an interview guide and field notes were used to collect the information towards the English learning needs for DHH children. The results of the study identified several needs that underlie the development of English multimedia learning materials, namely inadequate English instructors, text-based teaching materials, and the less than optimal teaching and learning process during the COVID-19 pandemic. Therefore, the development of multimedia-based English learning materials is needed.